Noncompliance with Ocular Hypertensive Treatment in Patients with Primary Open Angle Glaucoma among the Arab Population in Israel: A Cross-Sectional Descriptive Study - Muhannad Masoud; Adi Sharabi-Nov; Joseph Pikkel (Journal of Ophthalmology)
Objective. To evaluate the noncompliance treatment rates among primary open angle glaucoma (POAG) Arab patients in Israel and to verify the associated factors for noncompliance. Patients and Methods. A cross-sectional study took place using a questionnaire. Patients were initially interviewed and requested to answer a questionnaire. The questionnaire was developed based on a pilot test. Items included information about age, gender, number of prescribed drugs, and multiple reasons for noncompliance with drug therapy. Setting. Ophthalmologic HMO clinics, located in 3 Arab cities in the center of Israel. Participants. 400 Arab participants (197 men, 203 women) undergoing routine clinical care were recruited. Results. General rate of noncompliance, for both genders, was found to be 50%. Factors associated with nonadherence included inadequate knowledge (32%), underestimation of the disease severity (25.5%), and denial 15.5%. Compliance rates were unaffected by gender or number of prescribed drugs. Compliance was significantly higher in younger patients (age < 50) and in older patients (age > 80), 63% and 77%, respectively, (). Conclusion(s). Noncompliance was found to be common among an Arab population in Israel, particularly between the ages of 50 and 80. Educational programs, improving patient-physician relationship, and personalizing treatment could provide means for improved adherence.